1999
DOI: 10.1161/01.atv.19.11.2788
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Intimal-Medial Thickness and Stiffness Are Not Affected by Hypercholesterolemia in Uncomplicated Essential Hypertension

Abstract: Abstract-The combined effects of hypertension and hypercholesterolemia on carotid anatomy and stiffness were studied in 62 normotensives, 141 uncomplicated essential hypertensives with a total cholesterol level Ͻ240 mg/dL, and 60 essential hypertensives with a total cholesterol level Ն240 mg/dL. Carotid ultrasonography was performed to evaluate intimal-medial thickness (IMT), relative wall thickness, and the presence of plaque. Carotid pressure waveforms were recorded by applanation tonometry to measure caroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 67 publications
2
23
0
Order By: Relevance
“…For example, the augmentation index and indices of arterial stiffness have been shown to be independent of cholesterol levels in patients with hypertension and/or hypercholesterolemia. 13,14 Furthermore, cholesterol lowering with statin did not change the augmentation index or central arterial compliance in patients with hypercholesterolemia. 15,16 In contrast, elevated LDL cholesterol has been associated with increased central PP, augmentation index, and PP amplification in various patient groups.…”
Section: Discussionmentioning
confidence: 95%
“…For example, the augmentation index and indices of arterial stiffness have been shown to be independent of cholesterol levels in patients with hypertension and/or hypercholesterolemia. 13,14 Furthermore, cholesterol lowering with statin did not change the augmentation index or central arterial compliance in patients with hypercholesterolemia. 15,16 In contrast, elevated LDL cholesterol has been associated with increased central PP, augmentation index, and PP amplification in various patient groups.…”
Section: Discussionmentioning
confidence: 95%
“…Another clinical study found that IMT in hypercholesterolemic hypertensives was not significantly thicker than IMT in normocholesterolemic hypertensives. 38 A synergism between SBP and LDL for atherosclerosis is not supported by findings from cohort studies with incident coronary disease or mortality as end points. For example, in the Honolulu Heart Program, serum cholesterol and SBP are additive (rather than synergistic) in logistic or probit models of coronary heart disease risk (J.H.…”
Section: Discussionmentioning
confidence: 99%
“…97 Accordingly, no significant correlation between cholesterol levels and local (carotid Young's elastic modulus and b stiffness index) 98 or systemic (total arterial compliance) 99 indices of arterial stiffness was found in populations with a high prevalence of atherosclerosis. Conversely, central pulse pressure and augmentation index have been found increased in patients with hypercholesterolemia.…”
Section: Impact Of Arterial Structure and Function On Ventricular Loamentioning
confidence: 99%